FARM SIZE EFFICIENCY DIFFERENTIALS OF BIO-FORTIFIED CASSAVA PRODUCTION IN NIGERIA: A STOCHASTIC FRONTIER ANALYSIS APPROACH - Kolapo Adetomiwa (Zibeline International, 2021)
The study specifically investigated farm size efficiency differentials of bio-fortified cassava production in Nigeria. Data were collected through a cross-sectional survey of bio-fortified cassava producers in Nigeria. The estimated coefficients of the parameters of production variables for small scale bio-fortified cassava farm size (land, herbicide and fertilizer) played a major role in bio-fortified cassava production on a small scale in Nigeria. For the medium and large scale bio-fortified cassava farm size, production variables (land, labor and fertilizer) and (land, labor, herbicide and fertilizer) respectively played a major role in bio-fortified cassava production. The average economic efficiency of the small, medium and large scale bio-fortified cassava producers was 42%, 54% and 63% respectively. Policies intended to increase the popularization and cultivation of bio-fortified cassava in Nigeria should be targeted toward the small and medium scale cassava farmers since they carried the majority of the producer of bio-fortified cassava in Nigeria.